NILAI MORAL DALAM NOVEL ANAK-ANAK SEMAR KARYA SINDHUNATA - Nurnani, Dewi (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2024)
This article entitled Nilai Moral Dalam Novel Anak-Anak Semar Karya Sindhunata (Moral Values in the Novel Anak-Anak Semar by Sindhunata) aims to describe the moral values contained in the novel Anak-Anak Semar by Sindhunata. This research uses a qualitative descriptive method with a structural approach. The writer reads the novel Anak-Anak Semar by Sindhunata, understands its structural elements and then concludes, based on the interrelationship of these elements, what moral values the author wants to convey to the reader. The results of this study show that moral values are related to (1). the human relationship with oneself, namely feelings of self-confidence, sadness, longing, arrogance, and ambition; (2). human relations with other humans include affection, sacrifice, love of country, disappointment, power, wealth, greed, and lies, as well as falsehood; and (3). Human relationship with God includes belief in God, death, immortality, patience, always remembering and being alert. It is hoped that this article can make a contribution in the form of learning moral values in human life, social and state life, to society in general and children in particular.